SIPA1L3 identified by linkage analysis and whole-exome sequencing as a novel gene for autosomal recessive congenital cataract - Evers, Christina; Paramasivam, Nagarajan; Hinderhofer, Katrin; Fischer, Christine; Granzow, Martin; Schmidt-Bacher, Annette; Eils, Roland; Steinbeisser, Herbert; Schlesner, Matthias; Moog, Ute (European journal of human genetics, 2015)
Congenital cataract (CC) is one of the most important causes for blindness or visual impairment in infancy. A substantial proportion of isolated CCs has monogenic causes. The disease is genetically heterogeneous, and all Mendelian modes of inheritance have been reported. We mapped a locus for isolated CC on 19p13.1-q13.2 in a distantly consanguineous German family with two sisters affected by dense white cataracts. Whole-exome sequencing identified a homozygous nonsense variant c.4489C>T (p.(R1497*)) in SIPA1L3 (signal-induced proliferation-associated 1 like 3) in both affected children. SIPA1L3 encodes a GTPase-activating protein (GAP), which interacts with small GTPases of the Rap family via its Rap-GAP-domain. The suggested role of Rap GTPases in cell growth, differentiation and organization of the cytoskeleton in the human lens, and lens-enriched expression of the murine ortholog gene Sipa1l3 in embryonic mice indicates that this gene is crucial for early lens development. Our results provide evidence that sequence variants in human SIPA1L3 cause autosomal recessive isolated CC and give new insight into the molecular pathogenesis underlying human cataracts.
Gesehen am 20.07.2020